Subjective and objective sleep disturbances following trauma-focused treatment: clinical research article - Porten, Salomé; Friedmann, Franziska; Schoofs, Nikola; Barth, Charlotte; Meyer, Kristina; Santangelo, Philip; Ebner-Priemer, Ulrich; Müller-Engelmann, Meike; Steil, Regina; Kleindienst, Nikolaus; Enning, Frank; Fydrich, Thomas; et al. (European journal of psychotraumatology, 2025)
Background: Most individuals with posttraumatic stress disorder (PTSD) report sleep disturbances. Yet, results on the impact of trauma-focused therapy on subjective and objective sleep disturbances are inconsistent. Objectives: This study conducted secondary analyses from a randomized controlled trial (RCT; German Clinical Trials Registration: DRKS00005578) to investigate changes in both subjective and objective sleep over the course of trauma-focused therapy and whether these changes differed for dialectical behaviour therapy for PTSD (DBT-PTSD) or cognitive processing therapy (CPT). Methods: Women with PTSD related to childhood abuse were randomized to receive DBT-PTSD or CPT. Sleep was assessed in n = 180 women using the Pittsburgh Sleep Quality Index (PSQI), sleep diaries, and actigraphy at baseline, 6 and 12 months into treatment, with sleep monitoring for 1 week at each assessment. Results: Subjective sleep disturbances improved significantly from pre- to post-treatment, reflected in better PSQI scores (d = 0.76), sleep quality (d = 0.69), and total sleep time (d = 0.11) in sleep diary entries with no differences between treatment groups. No significant changes were observed in actigraphy measures. In total, 76% of participants still met the clinical cut-off of 5 on the PSQI, indicating clinically significant subjective sleep disturbances. Conclusions: PTSD treatments were linked to improvements in subjective sleep quality, but objective sleep measures remained unaffected. A high percentage of participants with persistent clinical sleep disturbances after treatment highlight the need for further research on the efficacy of PTSD treatments on sleep disturbances. To reduce the burden of sleep disturbances, sleep-specific treatment components may need to be added to trauma-focused treatments. Trauma-focused therapies were associated with moderate subjective, but no objective improvements in sleep.Sleep changes did not differ between individuals undergoing 12 months of cognitive proccessing therapy versus dialectical behaviour therapy for PTSD.The majority of patients (76%) still displayed clinically significant subjective sleep disturbances after PTSD treatment, whereas objective measures did not detect disturbed sleep from the start. Trauma-focused therapies were associated with moderate subjective, but no objective improvements in sleep. Sleep changes did not differ between individuals undergoing 12 months of cognitive proccessing therapy versus dialectical behaviour therapy for PTSD. The majority of patients (76%) still displayed clinically significant subjective sleep disturbances after PTSD treatment, whereas objective measures did not detect disturbed sleep from the start.
Gesehen am 11.11.2025